CENTERED LEARNING APPROACH SEBAGAI MEDIA PENGEMBANGAN KECERDASAN JAMAK ANAK USIA DINI (STUDI KASUS DI TK ISLAM PLUS MUTIARA YOGYAKARTA) - Yurita Erviana (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
This study is aimed to describe student centered learning approach to develop multipleintelligences on early childhood in kindergarten Islamic Plus Mutiara Yogyakarta. Theobject of this research is student centered learning approach as a media to develop multipleintelligences on early childhood in kindergarten Islamic Plus Mutiara Yogyakarta. Thisresearch is qualitatif research use case study approach to seeing a social phenomena(a case) was happened in islamic Plus Kindergarten Mutiara Yogyakarta. Technique indata collection through observation, interview and documentation. Analysis data usingby descriptive qualitatif with interactive analysis model. The reseach data validity itwas tested again by using triangulation and indepth observation. The result show thatof student centered learning approach is one of learning approach in Islamic PlusKindergarten Mutiara Yogyakarta doing by giving a freedom to child to make a changeand to establish play or learning activity. Another that, the child demand to getting activein learning proces. The another was find that the child getting facilitation to developtheir intelligence by activity well choosen by child with supported by resource learningequality.